Cryopreservation Maintains Functionality of Human iPSC Dopamine Neurons and Rescues Parkinsonian Phenotypes In Vivo - Dustin R. Wakeman; Benjamin M. Hiller; David J. Marmion; Christopher W. McMahon; Grant T. Corbett; Kile P. Mangan; Junyi Ma; Lauren E. Little; Zhong Xie; Tamara Perez-Rosello; Jaime N. Guzman; D. James Surmeier; et al. (Stem Cell Reports, 2017)
A major challenge for clinical application of pluripotent stem cell therapy for Parkinson's disease (PD) is large-scale manufacturing and cryopreservation of neurons that can be efficiently prepared with minimal manipulation. To address this obstacle, midbrain dopamine neurons were derived from human induced pluripotent stem cells (iPSC-mDA) and cryopreserved in large production lots for biochemical and transplantation studies. Cryopreserved, post-mitotic iPSC-mDA neurons retained high viability with gene, protein, and electrophysiological signatures consistent with midbrain floor-plate lineage. To test therapeutic efficacy, cryopreserved iPSC-mDA neurons were transplanted without subculturing into the 6-OHDA-lesioned rat and MPTP-lesioned non-human-primate models of PD. Grafted neurons retained midbrain lineage with extensive fiber innervation in both rodents and monkeys. Behavioral assessment in 6-OHDA-lesioned rats demonstrated significant reversal in functional deficits up to 6 months post transplantation with reinnervation of the host striatum and no aberrant growth, supporting the translational development of pluripotent cell-based therapies in PD.